Public, like a frog - Jasmine Donahaye (The Writer in the Academy: Creative Interfrictions, 2011)
This chapter examines definitions of creative non-fiction and the intersection of creative writing and academic research, and queries the conventions of academic writing, calling for a more personally engaged kind of literary criticism. It discusses responses to Emily Dickinson, Peter Cole, Homi Bhabha, Robert Southey, George Orwell, Edward Said, Thom Gunn and others.